(untitled) (ModaPalavra e-periódico, 2019)
In the fashion universe, illustrations are very important to publicize products or brands and the fashion illustrations are the beginning to building a product. In the fashion illustration, the graphic elements as dot, line, surfaces and blots are the basis to represent the figures from this universe. In this sense, expressivity and perception occur both through the aesthetic and formal aspects, as well as the symbolic ones, which are organized in a certain way, become quite relevant, since its main objective is to promote an idea or concept and to establish an impact On the viewer. For this, the present article makes a synthesis on the concepts of visual syntax, aesthetic-formal elements and symbolic associations and seeks to apply this theory in the reading of an illustration by Laura Laine, perfecting the understanding about the image to which it refers and making analogies Of this image with others it mentions.This article aims to present na analysis of the early stages of the product development process in fashion and clothing, seeking to outline how the information is used by the designer, as a professionalresponsible for creating. With the lócus of Recife city, Brazil, and as an object of research in creative companies of Fashion Design.